Propuesta para la creación de estrategias de promoción para el fomento del turismo religioso experiencial en la ciudad de Ibarra - Pasquel Quintana, María Augusta (2023)
San Miguel de Ibarra stands out notably for its undeniable potential in the tourism field, as it is home to grandiose and impressive churches that are essential elements in the rich cultural and religious heritage of the town. These magnificent architectural constructions exert a magnetic attraction on visitors seeking various purposes, such as rest, spiritual enrichment, cultural immersion and other equally varied purposes. In this context, the central purpose of this research lies in the evaluation of the intrinsic potential of experiential religious tourism in the region, simultaneously with the formulation of promotional strategies aimed at optimizing the development of this tourism modality. The proposed methodology for the study is based on a hybrid research approach that combines qualitative and quantitative elements. Likewise, the application of analytical-synthetic and deductive approaches is valued to guide research effectively. To enrich this structure, three fundamental research techniques are integrally incorporated: observation, interviews and surveys. To achieve this objective, a non-probabilistic convenience sample is chosen, involving a group of 166 tourists who visit various churches in the canton of Ibarra. The results obtained generate a detailed vision of the current situation of religious tourism in the aforementioned canton, while deepening the understanding of the factors that motivate tourists to choose these places of worship as destinations. It is concluded that religious tourism provides considerable benefits by providing enriching and evocative experiences to each individual who chooses to participate in this form of tourist activity